Gender, political participation and electoral systems: A cross‐national analysis. (20th December 2013) - Beauregard, Katrine
Abstract This article investigates whether the smaller gender gaps in political engagement, found in more proportional electoral systems, translate into smaller gender differences in political participation. Using data from the Comparative Study of Electoral Systems, it presents the argument that more proportional systems may send signals that multiple interests are included in the policy‐making process, which may increase women's levels of political participation and thereby reduce gender gaps. Additionally, the article tests for the possibility that a greater number of political parties and the elected representatives they provide act as barriers to political participation that have a greater impact on women's levels of participation than men's. It is argued that women's lower levels of political resources and engagement might create more difficult barriers for them than for men. Results lend little support for the first hypothesis, but a greater confirmation for the second.